Curriculum Innovation Management in Islamic Integrated Schools - Arif Rahman Syarif; Azisah, St.; Latuconsina, Nur Khalisah (Jurnal Pendidikan Dasar dan Keguruan, 2026)
Education plays a crucial role in Indonesia's national development by investing in high-quality, innovative, and morally upright human resources. The qualitative case study method employs observation, interviews with the principal, teachers, students/alumni, curriculum team, and document analysis including the School Education Curriculum (KSP) and evaluation reports. Research findings show that curriculum innovation management at SMKIT Ibnul Qayyim Makassar implements the vision "Hafizh Qur'an, Jago Komputer" to integrate Software Engineering (RPL) vocational education with Islamic values. This holistic approach combines mandatory Qur'an memorization (minimum 2.5 Juz), Sharia-compliant Teaching Factory (TEFA) such as IQIS Software Factory, 4-6 month Industrial Work Practice (PKL), Project Based Learning (PBL), and hidden curriculum elements like morning dhikr and Dhuha prayer. Management strategies encompass the cycle of planning, organizing, actuating, and controlling, supported by industry partnerships (DUDI), parenting programs, as well as strengthening foreign languages and entrepreneurship. Findings demonstrate successful dual competency integration: RPL hard skills relevant to Industry 4.0 (certifications, real projects) and Islamic soft skills (integrity, discipline), recognized by DUDI as superior to other vocational school graduates. This innovation addresses curriculum-industry gaps. The conclusion affirms this model as a national reference for Islamic vocational schools, with recommendations to strengthen stakeholder collaboration for long-term impact. The research contributes to the Merdeka Curriculum and Indonesia's quality human resource development in the globalization era.